Beberapa premis tentang perasaan hasad-dengki (PHD) sebagai nilai masyarakat Melayu : suatu polemik? - Abd. Hamid Mohd. Azhar, Balwi Mohd. Koharuddin, Othman Muhamed Fauzi, Md. Shah Azmi (N/A, 2004)
Beberapa premis tentang perasaan hasad-dengki (PHD) sebagai nilai masyarakat Melayu : suatu polemik? by Abd. Hamid Mohd. Azhar, Balwi Mohd. Koharuddin, Othman Muhamed Fauzi, Md. Shah Azmi,